2012
DOI: 10.4172/2155-9546.1000166
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Haematological Indices and Some Biochemical Enzymes of Juveniles Clarias gariepinus (Burchell 1822) Fed Varying Levels of Moringa oleifera Leaf Meal Diet

Abstract: The study examined the utilization, hematological and biochemical enzymes of Clarias gariepinus juveniles fed varying levels of Moringa oleifera leaf meal diets for a period of 8 weeks. Moringa oleifera leaf meal substituted fish meal at 0% (control), 10%, 20%, 30%, 40% and 50% in the six different diets. Clarias gariepinus juveniles (mean weight 29.69 ± 0.91 g) were randomly distributed into 18 concrete tanks at 10 fish/tank in triplicate treatments and were fed twice daily at 8.00 hrs-9.00 hrs and 17.00 hrs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
29
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 22 publications
8
29
2
1
Order By: Relevance
“…The lack of variation (p>0.05) in platelet count of from the initial value to 40% BSSM treatment and from 60% to 100% BSSM treatments suggests that platelets were not affected by the dietary treatments. The reduced platelet count for fish fed 60% to 100% BSSM-included diets may be due to fish reaction to the effect of the presence of anti-metabolites in the diets and this agrees with the findings of Fagbenro et al (2007) and Ozovehe (2013).…”
supporting
confidence: 91%
“…The lack of variation (p>0.05) in platelet count of from the initial value to 40% BSSM treatment and from 60% to 100% BSSM treatments suggests that platelets were not affected by the dietary treatments. The reduced platelet count for fish fed 60% to 100% BSSM-included diets may be due to fish reaction to the effect of the presence of anti-metabolites in the diets and this agrees with the findings of Fagbenro et al (2007) and Ozovehe (2013).…”
supporting
confidence: 91%
“…However, the finding of Ayotunde & Ofem, (2008) who reported significant decrease in haemoglobin of O. niloticus at a concentration of 5.0 mg of pawpaw seed extract per litre of culture water further suggest that dosage and mode of administration of PSM could lead to differentiation in the outcome of studies of different experiments. This result also agrees with the findings of Ozovehe (2012) who reported no significant influence of Moringa oleifera on the WBC of Clarias gariepinus. Ayotunde et al (2010), however, reported significant decreased in the levels of WBC of O. niloticus fed PSM.…”
Section: Discussionsupporting
confidence: 93%
“…There was a decrease in the RBC count with increase of Moringa above 10% inclusion rate. This reduction is similar to the reports on inclusion of Moringa in the diet of C. gariepinus with inclusion levels of above 10% (Ozovehe, 2013;Dienye and Olumuji, 2014). The Haemoglobin (Hb) and Haematocrit (PCV) were in the range 4.16 -4.75 g/dL and 13.42 -15.28% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The Hb and PCV results also decrease at the inclusion rate of above 10% Moringa similar to RBC counts. The decrease in RBCs, Hb and PCV with increased Moringa inclusion could be as a result of higher anti-metabolites which are toxic in the diet of the fish, especially tannin (Ozovehe, 2013;Dienye and Olumuji, 2014 (Bittencourt et al, 2003). The MCV is also within the range of 115-183fL for hybrid tilapia (Hrubec et al, 2000) and 121.67 -299.33fL for Oreochromis andersonii (Kefi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%